Uso de diatomáceas na reconstrução paleolimnológica em planície de inundação - Ruwer, Daiane Trevisan (2017)
The geomorphology of the high Paraná River floodplain depends directly on the natural hydrological regime. This relationship is evidenced by a continuous landscape complexity, which results in new environments, which alter composition and diversity. The organisms that respond effectively to these modifications and that have great affinity with the habitat are the bioindicators, as the diatoms. These to be incorporated and to be preserved in the sediment easily are also used as an important indicator group of paleolimnological studies. Therefore, the aim of this work was to use the fossil and current diatoms and to relate their succession and autoecology to geomorphological processes occurring in a fluvial island of the Upper Paraná River floodplain. Hypothesizing that community of fossil diatoms will respond to local environmental changes, through changes in composition, richness, abundance and guilds along the vertical gradient of the sediment. For this, a record was collected on an island located in the central zone of the main channel of the Paraná River. With continuous layers of the record was possible to make permanent slides for the quantitative and qualitative analysis of the diatoms. The results of this study were divided into two segments, the first entitled Temporal geomorphological changes based on the succession of fossil diatoms , in which it was reported that the composition, richness, abundance and guilds of diatoms changed successively in relation to the geomorphological periods. In the second segment titled Community of periphytic diatoms and sediment: a paleoecological and taxonomic approach it was possible to contribute with the autoecology and taxonomic information of the species along the environmental changes. In view of this, all the results presented demonstrate that the diatom flora presents a great biomonitoring potential of environmental and geomorphological changes. And that the floristic and distribution pattern and ecological information of the species can be used to infer background information in the past for predictions of compositions of future species.